If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.67 = ln(y) Multiply ln * y 0.67 = lny Solving 0.67 = lny Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1lny' to each side of the equation. 0.67 + -1lny = lny + -1lny Combine like terms: lny + -1lny = 0 0.67 + -1lny = 0 Add '-0.67' to each side of the equation. 0.67 + -0.67 + -1lny = 0 + -0.67 Combine like terms: 0.67 + -0.67 = 0.00 0.00 + -1lny = 0 + -0.67 -1lny = 0 + -0.67 Combine like terms: 0 + -0.67 = -0.67 -1lny = -0.67 Divide each side by '-1ny'. l = 0.67n-1y-1 Simplifying l = 0.67n-1y-1
| h=16t^2+vt+s | | 12+(5-9)= | | 3.2d=15.75+54.15 | | 7-x=7x+39 | | 6x+2x-9=95 | | -5x-2=x-2 | | 20x+35x=121 | | 5-2(x+2)=13 | | 14x-3+30=16x+11 | | x/3*4=20 | | 95=8x-8 | | 5+2(3x-8)=2x+9 | | 11+d+(-4)ford=-6 | | k^2-32k+8=0 | | 3(8.2-x)=6.6 | | -2(3x-2)=4-6x | | 26=6(5-a)+2 | | 7*5=63-N | | x/34=20 | | 56=t-25 | | 12x+11+69=25x+2 | | -5x-4=-3x+10 | | -10p-8=2 | | 3x+10y=-4 | | 63x^3+108x^2+81x= | | 2u-3=3 | | 6x+7=-2+7x | | 7x^2+12x+9= | | 7x-4(x+5)=16 | | x-10=-38+5x | | 42x^2-41x-8=0 | | 31+25x=-5-5 |